2020
DOI: 10.1016/j.esxm.2020.100292
|View full text |Cite
|
Sign up to set email alerts
|

Variations in the Number of Patients Presenting With Andrological Problems During the Coronavirus Disease 2019 Pandemic and the Possible Reasons for These Variations: A Multicenter Study

Abstract: Introduction COVID-19 pandemic caused unprecedented restrictions in outpatient services and surgical practices in urology as in other medical branches as well as in all areas of life. Aim To investigate whether there have been variations in the presentations of male patients with sexual and reproductive health problems to the outpatient urology clinics during the COVID-19 pandemic and to understand the underlying factors for these variations, if any. Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 17 publications
1
13
0
3
Order By: Relevance
“…A retrospective chart review of 12 outpatient urology clinics across Turkey investigated whether there have been variations in the presentations of male patients with sexual and reproductive health problems during the COVID-19 pandemic. 10 Andrological problems (i.e., ED, premature ejaculation, Peyronie's disease, and priapism, varicocele, infertility, primary/secondary hypogonadism, anejaculation, spermatocele, and undescended testicles) were detected in 721 of 4,955 male patients included in the study. Study findings showed that there was a significant increase in overall andrological diagnosis in these patients during the pandemic period compared with the pre-pandemic period (n = 293 [17%] vs n = 428 [13.2%], p < 0.001, respectively) ( Figure 3 ).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…A retrospective chart review of 12 outpatient urology clinics across Turkey investigated whether there have been variations in the presentations of male patients with sexual and reproductive health problems during the COVID-19 pandemic. 10 Andrological problems (i.e., ED, premature ejaculation, Peyronie's disease, and priapism, varicocele, infertility, primary/secondary hypogonadism, anejaculation, spermatocele, and undescended testicles) were detected in 721 of 4,955 male patients included in the study. Study findings showed that there was a significant increase in overall andrological diagnosis in these patients during the pandemic period compared with the pre-pandemic period (n = 293 [17%] vs n = 428 [13.2%], p < 0.001, respectively) ( Figure 3 ).…”
Section: Discussionmentioning
confidence: 98%
“…The number of patients diagnosed with ED during the pandemic was significantly higher during COVID-19 compared to the pre-COVID-19 pandemic period (n = 150 [8.7%] vs n = 214 [6.6%], p = 0.008) ( Figure 3 ). 10 The authors hypothesized that possible reasons for more frequent presentation to the outpatient urology clinics with ED may include relationship strain due to the “Stay Home” policies, job losses and economic problems, and increased anxiety and depression. Limitations of this study include its retrospective design, lack of randomization, differences in patient baseline characteristics between the comparison groups, and potential confounding from unknown and/or unmeasured variables.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported issues around sexual and reproductive health amidst the pandemic [ 29 ]. Duran et al [ 36 ] investigated whether there has been an increase in the number of patients presenting with sexual and reproductive health issues during the pandemic and found an increase in andrological diagnoses, male reproductive or sexual health problems and erectile dysfunction. The authors conclude that although the etiology is multifactorial, psychological factors seem to play a vital role.…”
Section: Discussionmentioning
confidence: 99%
“…44 During the COVID-19 pandemic period, it was reported that there was a significant increase in the diagnostic rate of ED among male patients presenting to the outpatient urology clinics compared with the pre-COVID-19 pandemic period. 23 An online survey on the sexual health of 217 males through IIEF-5 questionnaire reported 31.8% of ED prevalence. 26 Moreover, ED was seen at higher rates in the healthcare professionals group compared with the control group.…”
Section: Discussionmentioning
confidence: 99%
“…Published literature also demonstrated that erectile dysfunction (ED) is a likely consequence of COVID-19 for survivors and reviewed the possible mechanisms contributed to the potential onset of ED. 22 Together with the number of outpatients diagnosed with ED markedly increased during the pandemic 23 and some studies reported ED in other male subgroup, 14 , 24 , 25 , 26 it is most likely that COVID-19 patients may develop ED. However, currently, the erectile function in male recovered patients with COVID-19 remains unknown.…”
Section: Introductionmentioning
confidence: 99%